Downtime Cost Analysis of Offloading Operations Considering Vessel Motions and Mooring Responses in Malaysian Waters - Patel, M.S. (Institute of Electrical and Electronics Engineers Inc., 2019)
A real time motion of moored FPSO in side-by-side configuration for regular wave is simulated in ANSYS AQWA to evaluate the structure motion responses and cable forces under criteria and operational wave conditions for two sea-state. The mooring failure is simulated wherein whole cable tensile forces are calculated. Downtime occurs when the vessel motion and cable responses in operating wave conditions exceed the safe limiting values. With the help of a real time wave scatter diagram of three different locations in Malaysian waters, the probability occurrences are obtained and finally a novel study on the downtime cost analysis for offloading operations is performed considering structure responses and mooring failure conditions. In this paper, a successful attempt has been made to connect vessel motion responses to cost. This paper evaluates the possible downtime cost and economical risks involved in the different locations of Malaysian waters for offloading operations. Â© 2019 IEEE.